4a minus 6b supra 6a minus 9b
Răspunsuri la întrebare
Răspuns de
6
(4a - 6b)/(6a - 9b) =
= 2×(2a - 3b) / 3×(2a - 3b) =
(se simplifica 2a-3b)
= 2/3
= 2×(2a - 3b) / 3×(2a - 3b) =
(se simplifica 2a-3b)
= 2/3
Răspuns de
1
(4a-6b)/(6a-9b)=
2×(2a-3b)/3×(2a-3b)=
=2/3 coronita te rog!
2×(2a-3b)/3×(2a-3b)=
=2/3 coronita te rog!
Alte întrebări interesante
Engleza,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă